2017
DOI: 10.17240/aibuefd.2017.17.28551-304629
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmeni Adaylarının Başarı Yönelimleri İle Mesleki Kaygı Düzeylerinin İncelenmesi

Abstract: ÖZETBu araştırmanın amacı sınıf öğretmeni adaylarının başarı yönelimleri ve mesleki kaygı düzeylerinin cinsiyet ve sınıf düzeyi açısından incelenmek ve başarı yöneliminin mesleki kaygıyı yordayıp yordamadığını belirlemektir. Araştırmanın çalışma grubunu Erciyes ve Cumhuriyet üniversiteleri Eğitim Fakülteleri Sınıf öğretmenliği programlarında öğrenim gören ve basit tesadüfi eleman örnekleme yöntemiyle seçilen (%% 26,2'si erkek; %% 73,8'i kadın ) 321 öğrenci oluşturmaktadır. Araştırmada öğrencilerin başarı yönel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
1
2
0
4
Order By: Relevance
“…It was observed that the differences between the teaching efficacy levels of the physical education teacher candidates and the arithmetic averages of task-centered anxiety levels were not statistically significant in terms of gender, grade and sports branch. While this result is in line with some similar studies (Alrabai, 2015;Cheok & Wong, 2015;Erbaş, 2014), many similar studies have shown different results (Gözler, Bozgeyikli, & Avcı, 2017;McLean, Abry, Taylor, Jimenez, & Granger, 2017;Muñoz, Penalba, Sánchez, & Santos, 2017;Saracaloğlu, Kumral, & Kanmaz, 2009). In two different studies, it was observed that gender factor is an important variable and especially female teacher candidates' perception of teaching efficacy is high and their professional anxiety are at optimum level (Erbaş, 2014;Saracaloğlu et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…It was observed that the differences between the teaching efficacy levels of the physical education teacher candidates and the arithmetic averages of task-centered anxiety levels were not statistically significant in terms of gender, grade and sports branch. While this result is in line with some similar studies (Alrabai, 2015;Cheok & Wong, 2015;Erbaş, 2014), many similar studies have shown different results (Gözler, Bozgeyikli, & Avcı, 2017;McLean, Abry, Taylor, Jimenez, & Granger, 2017;Muñoz, Penalba, Sánchez, & Santos, 2017;Saracaloğlu, Kumral, & Kanmaz, 2009). In two different studies, it was observed that gender factor is an important variable and especially female teacher candidates' perception of teaching efficacy is high and their professional anxiety are at optimum level (Erbaş, 2014;Saracaloğlu et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…In the study conducted by Koç and Arslan (2015), a positive-moderate relationship was determined between achievement orientations and metacognitive awareness of reading strategies. Gözler et al (2017) found a negative-low-level relationship between achievement orientations and professional anxiety. In the study conducted by Arslan et al (2019), a positive-moderate relationship was found between students' lifelong learning tendencies and their attitudes towards reading habits.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 88%
“…Üniversite öğrencileri üzerinde gerçekleştirilen ve cinsiyet ile mesleki kaygı arasındaki ilişkileri konu alan çalışmalara bakıldığında farklı sonuçların ortaya çıktığı görülmektedir. Bu çalışmaların bir kısmında erkeklerin mesleki kaygı veya mesleki kaygı alt boyutlarına ait puan ortalamalarının, kadınların mesleki kaygı veya mesleki kaygı alt boyutlarına ait puan ortalamalarından anlamlı düzeyde yüksek olduğu tespit edilmiştir (Sadıkoğlu vd., 2018;Yalçınsoy, 2017;Gözler vd., 2017;Uygun vd., 2016;Uçak -Bindak, 2017;Karademir, 2018;Yangınlar, 2019). Bu çalışma sonuçlarının aksine, yine üniversite öğrencileri üzerinde yapılan diğer bazı çalışmalarda, kadınların mesleki kaygı puan ortalamalarının erkeklerin mesleki kaygı puan ortalamalarından anlamlı şekilde yüksek olduğu bulunmuştur (Akgün vd., 2007;Türkdoğan, 2014;Kula -Saraç, 2016,).…”
Section: Cinsiyet Değişkeni Ile Mesleki Kaygı Ve Hayatın Anlamı Arasındaki İlişkiunclassified